CIRAD organizations and publications - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
All CIRAD publications (shown below in brackets) contain at the least summaries in English (and Spanish) and some include entire articles in English. CEEMAT: Centre for study and experimentation on agricultural machinery (Machinisme agricole...